Atención de enfermería a la adolescente preeclámptica. Quito, 2019 - Karina Mishel, Karina Mishel (2019)
The health in young pregnant women could be in danger due to their social and food preferences. Also, they are vulnerable to the development of complications during pregnancy. One of them is preeclampsia; it requires nursing care directed to holistic assist to prevent complications in the mother/child dyad. It is descriptive and observational research with a sectional quantitative approach, to determine nursing care leading to the assistance to the adolescents preeclamptic in the Obstetric Center Service at the Provincial General Hospital "Pablo Arturo Suárez" since May to August, 2019. The sample was 12 nurses, and the permissions are getting for its implementation. A survey of knowledge validated by nine experts in Gineco-Obstetric and an observation guide processing in Excel and designed by "Piray and Riofrío." The knowledge lesser were: Assessment in biopsychosocial and spiritual fields, nursing diagnoses, a maintenance dose of magnesium sulfate. On the other hand, in the observation guide, the lesser valued by professionals was: Epigastralgia, osteotendinosos reflects and interpretation of laboratory results, prioritization of nursing diagnoses, education on the medication adverse effects. With the results gotten in this research, the knowledge and nursing care in this type of patients were able to see; for this reason, it contributed with a care plan, the nursing staff to serve as a guide.